Analisis Biaya Produksi dalam menentukan Harga Jual Pada Usaha Tahu Mas Boy Kota Langsa - Zulhilmi Zulhilmi; Ryanda Saputra; Desyana Putri; Ulfa Utari (AKUA: Jurnal Akuntansi dan Keuangan, 2026)
This study aims to analyze the calculation of production costs and determining selling prices at the Tahu Mas Boy Business in Langsa City using the full costing method. The problem faced by MSMEs, especially the tofu industry, is the lack of understanding in calculating accurate production costs, so that selling prices are often inaccurate and have an impact on low profitability and inaccurate profit and loss calculations of a business. The research method used is a descriptive qualitative approach with data collection techniques through observation, in-depth interviews, and documentation. Data analysis was carried out by comparing the calculation of the cost of production according to the company with the calculation using the full costing method. The results showed that the calculation of the cost of production using the full costing method produced a higher value than the calculation made by the Tahu Mas Boy Business. The results of the data analysis obtained according to the calculation of the Tahu Mas Boy Business of IDR 162 per piece, while using the full costing method it was IDR 179 per piece. According to the cost of production calculated by the Tahu Mas Boy Business, the selling price of large tofu is IDR 210, while according to the cost of production calculated using the full costing method, the selling price is IDR 228. There is a difference in the selling price per piece for tofu sold of IDR 18.